Examining the Relationship Between Perception of Cancer and Empathy: Descriptive Research - Karakaş, Neşe; Aktura, Seher Çevik; Özden, Gürkan; Sarıtaş, Seyhan Çıtlık (My University, 2023)
Objective: This study was conducted to determine the ef- fect of patients’ relatives’ empathy level on their perception of cancer. Material and Methods: This study was designed as descriptive re- search. It was carried out at a university hospital located east of Turkey. The universe of the research was constituted by patient relatives at the aforementioned hospital and other healthy individuals. Data were col- lected using the Personal Introduction Form, the Questionnaire for Mea- suring Attitudes Toward Cancer (Cancer Stamp)-Community Version, and the Empathy Level Scale designed by the researchers of this study 1,006 relatives of patients constitute the sample of the study. Data were analyzed using descriptive statistics, independent samples t-test, cor- relation, regression, and Cronbach’s alpha reliability analysis. The re- sults of the analysis of the data collected for this study were evaluated within a 95% confidence interval, and significance was determined as p<0.05. Results: It was found that participants had positive perceptions of cancer, that their empathy scores were high, and that their cognitive empathy was higher than their social skills and emotional response. The presence of family members and the degree of relationship with them were important determinants for the questionnaire measuring attitudes toward cancer (cancer stigma) community version.Conclusion: In this study, a significant negative correlation was found between empathy and cancer-related perceptions. Respondents’ attitudes toward cancer were found to change positively as empathy increased.
Keywords: Empathy; patient relative; cancer perceptions